2021
DOI: 10.1177/09636897211024210
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Mitochondria Transplantation Rescues Hypoxia/Reoxygenation-Induced Mitochondrial Dysfunction and Neuronal Cell Death Involving the FUNDC2/PIP3/Akt/FOXO3a Axis

Abstract: Mitochondrial transplantation emerges as a novel therapeutic solution for ischemia/reperfusion injury (IRI) in various tissues. Platelets have recently been used in mitochondrial transplantation as readily-available donors of small-size platelet mitochondria (plt-mito). Interestingly, FUN14 Domain Containing 2 (FUNDC2), a protein highly-expressed in the outer membrane (OMM) of plt-mito, has been identified to maintain platelet survival under hypoxic condition. The current study determined whether and how FUNDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
2
7
0
4
Order By: Relevance
“…Therefore, we decided to measured platelet mitochondrial bioenergetics in our model. We observed that T2D mice show greater platelet mitochondrial respiration, which is consistent with hyperglycemia-induced increase in glucose metabolism [24] . However, there were no differences with Metformin treatment in any of the parameters we interrogated in T2D treated mice compared to controls (Fig5).…”
Section: Resultssupporting
confidence: 82%
“…Therefore, we decided to measured platelet mitochondrial bioenergetics in our model. We observed that T2D mice show greater platelet mitochondrial respiration, which is consistent with hyperglycemia-induced increase in glucose metabolism [24] . However, there were no differences with Metformin treatment in any of the parameters we interrogated in T2D treated mice compared to controls (Fig5).…”
Section: Resultssupporting
confidence: 82%
“…5). T2D mice show higher baseline platelet mitochondrial respiration (23), consistent with hyperglycemia-induced increase in glucose metabolism (24). There were no differences with Metformin treatment in any of the parameters we interrogated in T2D treated mice compared to controls (Fig.…”
Section: Resultssupporting
confidence: 54%
“…Certos estudos indicam que tais benefícios ocorrem através da reparação da maquinaria bioenergética, possivelmente se fusionando com mitocôndrias hospedeiras (COWAN et al, 2016;XIE et al, 2021). Outros estudos, observando sua localização perinuclear e as baixas taxas de internalização, sugerem que os benefícios atribuídos às mitocôndrias exógenas se encontram na alteração de mecanismos de sinalização e expressão gênica (ALEXANDER et al, 2021;SHI;LIU, 2021). O mais provável é que os efeitos terapêuticos observados sejam resultado da combinação de diversos mecanismos.…”
Section: Transplante De Mitocôndriasunclassified
“…Já mitocôndrias provenientes de músculo esquelético ou cardíaco costumam apresentar semelhantes taxas de internalização(WEIXLER et al, 2020). Alguns trabalhos reportaram baixas taxas de internalização de mitocôndrias exógenas, com variações de eficácias de 3-15%(MA et al, 2020;SHI;LIU, 2021), 15-30% (KITANI et al, 2014HUANG et al, 2016) e 50%(ROBICSEK et al, 2018). Um fator que pode aumentar a taxa de internalização é o estresse celular das células receptoras(BABENKO et al, 2018SUN et al, 2019.…”
unclassified